Systematic transformation of functional analysis model into OO design and implementation - Yang, Yong (2008)
In this thesis, we have presented a proposed model, DF net for the modeling of functional analysis models. DF net is an enhanced DFD model. Based on DF net, we have proposed a systematic approach for the precise and semi-automated transformation of functional analysis models into OO design and implementation. With the use of the proposed approach, in the requirements analysis stage, use-cases with more complex functions are realized and specified in DF nets. In the design stage, the resulting DF nets are transformed into OO design. Based on the design, in the implementation stage, program codes for class operations to implement the use-cases are merged and generated automatically based on the codes for the supporting classes. The proposed approach can be used seamlessly to complement existing OO approaches to realize use-cases with more complex functions. We have also discussed the details of a comprehensive prototype system that has been developed to implement the proposed approach. We have also evaluated the proposed approach through case studies. A comparison of the proposed approach with related approaches has also been discussed.